Scaling up from sentience: modularity, conscious broadcast, and a constitutive solution to the combination problem - Lacalli, Thurston (Frontiers in Psychology, 2025)
Complexity in biology typically has less complex evolutionary antecedents which, for consciousness, begs the question of how a fully elaborated and unified consciousness, as we experience it, would have been scaled up from what we can assume to have been simpler, or at least different, beginnings. This poses difficulties for some theories, but is much simplified if the contents of consciousness combine in a constitutive way, so the balance between contents can be adjusted by natural selection incrementally as required, across generations, in evolutionary time. This contrasts with theories postulating an integrative solution to the combination problem, and is easiest to conceptualize by supposing that conscious sensations arise from the action of modular entities, each of which, regardless of spatial location, contributes separately to the total experience. There are, in consequence, two very different models for consciousness: that it is (1) non-modular, non-local and fully integrated at a conscious level, the more conventional view, or (2) modular, local, and constitutive, so that integrative processes operating at scale are carried out largely if not exclusively in a non-conscious mode. For a modular/constitutive model that depends on a broadcast mechanism employing a signal, what may be most important is the amplitude of the signal at its source rather than how far it is propagated, in which case each module must be structured so its output has precisely controlled characteristics and adequate amplitude. A model based on signal amplitude rather than propagation over distance would still require that conscious sensations adapted to serve memory accompany cognitive functions over which they exert only indirect control, including language and thought, but fails to explain how a localized signal comes to be perceived as pervasive and global in character. In contrast, the problem with integrative models is the assumption that consciousness acts globally and only globally, which risks misdirecting attention, both in theory and experiment, to anatomical structures and neurophysiological processes that may have little to do with the processes by which conscious sensations are produced or how brains come to be aware of them.